Insights on the United Nations Sustainable Development Goals scope: Are they aligned with a 'strong' sustainable development?. (10th April 2020) - Giannetti, Biagio F.; Agostinho, Feni; Almeida, Cecília M.V.B.; Liu, Gengyuan; Contreras, Luis E.V.; Vandecasteele, Carlo; Coscieme, Luca; Sutton, Paul; Poveda, Carlos
Abstract: The seventh edition of the International Workshop "Advances in Cleaner Production" (IWACP) was held at Universidad de La Costa, Colombia, in June 2018. Thematic sections were held for allowing theoretical discussions and practical activities, with the main goal of supporting discussions on the United Nations Sustainable Development Goals (UN-SDGs). Participants provided their perception on the allocation of UN-SDGs as relevant for managing the main forms of capital (environmental, economic and social) within two different sustainability conceptual models: a "traditional" model (representing the interdependence and substitutability among the environment, social and economic capitals), and the five sectors sustainability model (5SenSu). Results show an unbalanced distribution of SDGs among the capitals for both sustainability models, with social capital perceived as the most relevant across the SDGs. Particularly, the environment as a resource provider supporting societal development is perceived as relevant only for SDG 6 (Clean Water and Sanitation). The main outcomes of the workshop emphasize the need for further efforts towards a more objective interpretation of policy goals in post Agenda-2030 initiatives. The SDGs must be clearly understood and have a scientific resonance to objectively support public policies. Sustainability models, such as the 5SenSu, have the potential to support a more balanced definition of sustainable development goals across the different dimensions of sustainability. Highlights: The UN SDGs should be fundamentally aligned to one or more sustainability conceptual models. Cleaner production experts of the 7th IWACP provided their perception on the 17 SDGs with sustainability conceptual models. The SDGs are not evenly distributed among the economic, social and environmental forms of capital. Social capital is the most representative among the SDGs, while environmental capital is relevant only for SDG 6. Balanced and objective interpretations of policy goals in post Agenda-2030 initiatives are claimed.